Modern antihyperglycemic agents prescribed in Russia for type 2 diabetes mellitus - Yury Ivanovich Suntsov (Endocrinology Research Centre, 2012)
Aims. To conduct an analysis of modern antihyperglycemic prescription patterns in type 2 diabetes mellitus (T2DM). Materials and methods. Russian DM State registry was studied. Results. We obtained absolute and comparative data on use of insulin analogues, dipeptidyl peptidase-4 (DPP-4) inhibitors and glucagon-like peptide-1 agonists in treatment of T2DM. Conclusion. Percentage of DPP-4 inhibitors and GLP-1 analogues in T2DM treatment patterns remains nominal and does not exceed0.2%, which is significantly lower than in the majority of other countries. Insulin analogues are prescribed considerably more frequentlyand currently appear to be the most promising agents for treatment of T2DM.